Managing conflict through communication - Cahn, Dudley D.; Abigail, Ruth Anna (Pearson, 2014)
Managing Conflict Through Communication helps students approach conflict constructively and learn more positive conflict management and resolution skills. Narratives and case studies make the material accessible and engaging to a diverse student audience. Discussion questions and exercises throughout the text provide a basis for classroom discussion and practical applications of concepts